1999
DOI: 10.1193/1.1586052
|View full text |Cite
|
Sign up to set email alerts
|

Toward Performance-Based Seismic Design of Structures

Abstract: A new performance-based plastic design procedure for steel moment frames is presented in this paper. The role of plastic analysis in seismic design of structures is illustrated. The ultimate design base shear for plastic analysis is derived by using the input energy from the design pseudo-velocity spectrum, a pre-selected yield mechanism, and an ultimate target drift. The proposed design procedure eliminates the need for a drift check after the structure is designed for strength as is done in the current desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 0 publications
0
99
0
Order By: Relevance
“…This implies that the equivalent static forces are derived primarily based on the elastic dynamic response of fixed-base structures without considering soil-structure interaction (SSI) effects. The efficiency of using the code-specified lateral load patterns for fixed-base building structures has been extensively investigated [6][7][8][9][10][11][12][13][14][15]. The results of these studies indicated that the current design approach, in general, does not lead to a uniform distribution of deformation demands in multi-story structures.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This implies that the equivalent static forces are derived primarily based on the elastic dynamic response of fixed-base structures without considering soil-structure interaction (SSI) effects. The efficiency of using the code-specified lateral load patterns for fixed-base building structures has been extensively investigated [6][7][8][9][10][11][12][13][14][15]. The results of these studies indicated that the current design approach, in general, does not lead to a uniform distribution of deformation demands in multi-story structures.…”
Section: Introductionmentioning
confidence: 91%
“…Leelataviwat et al [9] evaluated the seismic demands of mid-rise moment-resisting frames designed in accordance with Uniform Building Code [5]. They proposed improved load patterns using the concept of energy balance applied to moment-resisting frames with a pre-selected yield mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…n is the number of frame span in the specific direction and i h is the height of i'th story from base. Value of Mpc1 can be determined by using the condition that no soft story mechanism would occur in the first story, when a factor of 1.1 times the design lateral forces are applied on the frame (Leelataviwat S et al 1999). Assuming that plastic hinges form at the base and top of the first story columns, the corresponding work equation for a small mechanism deformation gives:…”
Section: Developing the Pbpd Methods For Dual Moment And Eccentricallymentioning
confidence: 99%
“…To solve this problem, the performance-based plastic design (PBPD) method has been introduced [Leelataviwat S et al (1999), Leelataviwat S et al (2007), Lee SS and Goel SC (2001), Dasgupta P et al (2004), Chao SH and Goel SC (2006a,b), Chao SH et al (2007), ]. The PBPD method is based on the energy method (Housner GW, 1956).…”
Section: Introductionmentioning
confidence: 99%
“…The performance based design (PBD) (SEAOC 1999;Leelataviwat et al 1999) introduces a new and general framework in seismic design of structures by defining performance levels and objectives. Thus, three to five structural performance levels are defined and should be achieved for increasing levels of earthquake actions by satisfying performance objectives for every performance level.…”
Section: Introductionmentioning
confidence: 99%